Dilute antimonide nitride for long wavelength infrared photodetection - Chen, X. Z. (2014)
InSb1−xNx materials were fabricated by direct nitrogen implantation into InSb wafer and they are characterized by X-ray diffraction, Hall measurement, X-ray photoelectron spectroscopy. In-N bonds are clearly demonstrated and other forms of nitrogen, such as antisites (NIn), interstitial N2 , also exist in the grown films. The ratio to the total nitrogen bonds formed in the materials varies with preparation conditions. The optical bandgap data confirmed bandgap narrowing due to the incorporation of nitrogen. Photoconductive and photovoltaic photodetectors are fabricated and the cut-off frequencies of up to 11.5 μm are demonstrated.